Estructura de la comunidad bentónica (infaunal) en el delta del Río Colorado, México - Villarreal Chávez, Guillermo (1999)
The benthic cornrnunity structure of the Colorado River delta, Mexico, was studied by digging cores in six points a10ng a line perpendicular to the coastline. Three cornrnunities were found. The external community is influenced by human activities, but the cornrnunity indexes are similar to others reported in the Iiterature for equivalent areas. The middle cornrnunity has the highest density and biomass in the area, apparently because of bioturbation created by the crab Uca princeps. The internal community is poor in density and biomass, possibly because of the instabilitycaused by erosion related to the tide flux.